2017
DOI: 10.1080/0284186x.2017.1290272
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for brain metastases in patients with metastatic colorectal cancer

Abstract: The incidence of BM was 8.8% in patients with mCRC who received third-line therapy. The most important risk factor for developing BM was lung metastases. Furthermore, rectal cancer, metachronous metastatic disease and long survival were linked to BM development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
3
19
1
Order By: Relevance
“…In that study, we identified 42 patients with brain metastases, of whom six developed brain metastases before start of CetIri treatment and 36 developed it later. We were not able to identify any significant association between the development of brain metastases and mutations in KRAS, NRAS, BRAF or PIK3CA genes [3]. In other studies, PIK3CA and RAS mutations (especially KRAS exon 2 mutations) have been connected with an increased risk of brain metastases [9,11,14].…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…In that study, we identified 42 patients with brain metastases, of whom six developed brain metastases before start of CetIri treatment and 36 developed it later. We were not able to identify any significant association between the development of brain metastases and mutations in KRAS, NRAS, BRAF or PIK3CA genes [3]. In other studies, PIK3CA and RAS mutations (especially KRAS exon 2 mutations) have been connected with an increased risk of brain metastases [9,11,14].…”
Section: Discussioncontrasting
confidence: 74%
“…In 73 patients, KRAS exon 2 and BRAF mutations had previously been identified using TheraScreen V R KRAS mutation kit and pyrosequencing, and no new mutation analysis was performed. This has been described previously [3].…”
Section: Specimen Characteristics and Assay Methodsmentioning
confidence: 94%
See 3 more Smart Citations